PREDICTIVE ANALYSIS OF SURFACE QUALITY-CANDIDA ALBICANS BIOFILM RELATIONS - Elena-Raluca Baciu; Irina Grădinaru; Ştefan Toma; Maria Baciu; Constantin Baciu; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2015)
Introduction The theoretical researches conducted aimed at determining the mathematic relations of functional dependence among three variable parameters: medium rugosity (Rz), the number of colony forming units (CFU) and the medium thickness of fungal cell layer ( ) characterizing the formation and growth of Candida albicans biofilm. Material and methods The influence of the finishing techniques was materialized by medium rugosity (Rz) measured for each polished surface whereas the process of formation and growth of cellular biofilms was highlighted by parameters (CFU) and ( ) whose values were determined by electronic microscopy SEM. The functional dependence among the three variables taken into consideration: (Rz, UFC and ) in case of the nonnoble dental alloy was solved by using Mathematica 8.0 programme. Results The analysis of real regression surface shows that the observance of the interdependence relation between Rz, UFC and parameters shall occur for values of Rz = 0.72...2.65 µm, to which shall correspond medium thicknesses of the cellular layer = 19.7...28.8 µm. Similarly, from the regression surface of the predictive values it results that the satisfaction of the regression function shall occur for values of Rz = 0.98...2.47 µm, whereas for parameter we will have the value interval: 17.8...23.6 µm. Conclusions For the samples of Kera N alloy under study, all theoretical values obtained by predictive analysis for the variable parameters Rz, CFU and show that the finishing techniques applied to the surfaces of metal components of prosthetic restorations shall exert their influence on the formation and growth of Candida albicans biofilms.